Managerial ownership and performance: A commentary essay - Cheung, Adrian (Elsevier, 2010)
Florackis, Kostakis, and Ozkan [Florackis, C., Kostakis, A., and Ozkan, A., 2008. Managerial ownership and performance, Journal of Business Research, forthcoming] empirically examine the exact nature of the relationship between managerial ownership and corporate performance in the framework of semi-parametric regression. This commentary explores the authors' contribution to the corporate governance literature in the light of recent advances in semi-parametric regression. The commentary also considers how Florackis et al.'s findings align with important, emerging work in the corporate governance literature.